Adsorption Behavior of Sugarcane Bagasse-Derived Activated Carbon as a Copper Removal - Amanah, Nur Layli; Manuputty, Alsello Diveni; Ramadhani, Fadila Arum; Floresyona, Dita; Nursanto, Eduardus Budi; Oktaviano, Haryo Satriya; Nugroho, Agung (Department of Physics, Sebelas Maret University, 2025)
This study aims to remove Cu2+ as a heavy metal inside the sample solution implementation. Eliminating heavy metals through activated carbon utilizes sugarcane bagasse's high carbon content, which is rich in cellulose, lignin, and hemicellulose. There are various methods for eliminating metal content, including activation using Acid 0.1 M Hydrochloric Acid (HCl), Base 0.1 M Sodium Hydroxide (NaOH), and without using activation media. The method considers the different ion Cu2+ initial concentrations and contact times. Detailed initial concentrations of Cu2+ were conducted using CuSO4 media for 2.5, 5, 10, and 15 ppm and 15, 30, 60, and 120 minutes for length of contact time. For the result, the transmittance of FTIR showed a primary functional group of Activated Carbon (AC) on SBAC-1, comprising O-H, C-O, and C=O. The Brunauer-Emmett-Teller (BET) analysis also shows the significant value reaching 458.607 m2/g surface area's adsorption and had qmax = 8.13 mg/g, the highest adsorption capacity. The plot brings about the adsorption mechanism as physiochemical & multilayer adsorption, with a physisorption layer with percent removal of Cu2+ at 81.3% at 30 minutes optimum time and optimum initial concentration of 5 mg/L with 82.2 % absorption on SBAC-1. The determination of Freundlich as the isotherm model is the most suitable mechanism of absorption for all process variations and generates a R2 value of 0.9731 for the SBAC-1 sample.